Demanda e acesso para atenção secundária em saúde bucal nos municípios do Consórcio Intermunicipal de Saúde das Vertentes - CISVER - MG - Júlio Cézar Couto de Barros (2020)
The creation of the Oral Specialty Centers based on the National Oral Health Policy was an important strategy capable of guaranteeing the expansion of access to specialized dental care. However, its unequal distribution across the national territory, combined with the high demand for specialized services, means that a portion of the population is still unassisted. This study aims to understand the demand and access for secondary care procedures in oral health of patients seen in primary care in the municipalities of the Intermunicipal Health Consortium of Strands.The descriptive analysis was performed using the SPSS for Windows version 18.0. The study was approved by the Research Ethics Committee of the Federal University of Minas Gerais (opinion 1.615.701). The research was supported by seven dentists who work in primary care in seven municipalities belonging to consortium, who registered, through electronic forms installed on personal smartphones, all patients seen in Primary Care who needed specialized oral health care during the period from September 2019 to March 2020, in addition to the registration of the required specialty and its outcome. At the end of the study, there were a total of 651 patients in need of specialized treatment, 374 (57.5%) of whom were female, 242 (37.2%) aged between 15 and 29 years and 236 (36, 3%) between 30 and 59 years. Regarding the level of education, 288 (44.2%) had elementary school and 154 (23.7%) high school. The specialty with the greatest need was Endodontics, with a record of 336 patients (51.6%), of which 121 (65.40%) had endodontic treatment performed in Basic Units or in a service accredited by SUS. It was also observed that 275 (81.84%) patients had only one element in need of endodontic treatment, with the first molar being the most affected permanent tooth, with 114 elements (42.5%). The present study showed that, despite the undeniable advances achieved by Brazilian public health over the last few years, new strategies still need to be adopted in order to guarantee access and integrality of care, especially in relation to oral health. Therefore, the criteria for implementing the CEOs should be reviewed, or smaller specialized services, municipal or between associations of municipalities, should be implemented and appropriate to the different realities in health, in articulated with primary care, based on the epidemiological profile of the local population and local social indicators.